2022
DOI: 10.3389/fcimb.2022.884411
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas12a-Based Diagnostic Platform Accurately Detects Nocardia farcinica Targeting a Novel Species-Specific Gene

Abstract: Under the COVID-19 pandemic background, nucleic acid detection has become the gold standard to rapidly diagnose the infectious disease. A rapid, low cost, reliable nucleic acid detection platform will be the key to control next potential pandemic. In this study, a nucleic acid detection platform, which combined CRISPR/Cas12a-based detection with loop-mediated isothermal amplification (LAMP), was developed and termed CRISPR-CLA. In the CRISPR-CLA system, LAMP preamplification was employed, and CRISPR/Cas12a-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, five samples showed positive results by qPCR, whereas they were negative by our CRISPR-based approach and culture. Although we cannot exclude the possibility that the limit of detection (LOD) of qPCR is lower than our method and the five positive qPCR samples corresponded to much lower inoculums, in our previous study ( 13 ) qPCR showed a similar LOD to a CRISPR-based assay but generated some false-positive results.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, five samples showed positive results by qPCR, whereas they were negative by our CRISPR-based approach and culture. Although we cannot exclude the possibility that the limit of detection (LOD) of qPCR is lower than our method and the five positive qPCR samples corresponded to much lower inoculums, in our previous study ( 13 ) qPCR showed a similar LOD to a CRISPR-based assay but generated some false-positive results.…”
Section: Discussionmentioning
confidence: 67%
“…The use of guide RNA (gRNA) makes CRISPR/Cas-based detection extremely specific. However, most CRISPR-based detection platforms require two separate fluid-handling steps, namely, preamplification and CRISPR-based detection steps, resulting in multiple operations with the potential for contamination ( 12 14 ). More recently, a one-pot, one-step CRISPR-based nucleic acid detection technology, named CRISPR-top, has been successfully devised and applied to the diagnosis of coronavirus disease 2019 ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the feasibility and practicality of this diagnostic method in the eld, time and temperature were optimized in our preliminary study, and the nal reaction conditions selected were consistent with the results described by Wang et al [26]. Moreover, in terms of sensitivity, we used the results of recombinant plasmid (10 copies/μl) and pure bacterial nucleic acid (10 fg) compared with qPCR, CRISPR-CLA, CRISPR-CPA methods (10 2 copies/μl, 100 fg, 1 pg), respectively, and the results showed that the sensitivity was higher than that of other methods [19,20,24].…”
Section: Discussionmentioning
confidence: 72%
“…In this study, a novel assay was established for the detection of N. farcinica. The RT-RAA assay was performed at a constant temperature of 39°C for 20 minutes, which provides a signi cantly simpli ed operation and saved turnaround time compared to the cases with existing methods for detecting N. farcinica [19,24]. Furthermore, the assay protected the reaction from contamination (a one-step closed tube reaction) and was not dependent on complex thermal cyclers and skilled personnel, indicating that it can be applied in primary hospitals and communities with portable equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation